Recent Issues in the Implementation of the New Basel Minimum Capital Requirements for Market Risk - J. Orgeldinger (Ital Publication, 2018)
The Basel Committee suggested new ways of dealing with market risk in banks’ trading and banking books, in its October 2013 consultative paper, and subsequent versions published thereafter, for revised market risk framework FRTB. The Basel Committee estimates that the new rules will result in an approximate median capital increase of 22% and a weighted average capital increase of 40% (BCBS 2016), compared with the current framework. Budget reports on FRTB implementation range from costs of 5-million USD to 250-million USD. Key changes can be found in the internal model approach, in the standard rules and in the approval process. Significant changes introduced by the FRTB include stricter separation of the trading and banking book. Regardless of whether they use standardized or internal models, banks will need to review their portfolios to determine if existing classifications of instruments and desks as trading or banking book are still applicable, or whether a revision of desk structure is needed. In its article ‘Critical appraisal of the Basel fundamental review of the trading book regulation’ (Orgeldinger 2017) the theoretical foundations of the internal model approach IMA were analysed and the criticisms for FRTB risk models were investigated. A recent onslaught of rules is rendering the existing timeline for implementation practically impossible. In this article we present and critically evaluate different approaches to implement the new rules suggested by academics and major consulting companies.